(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study explores the structure of law in public health in the United Provinces (UP), in British India, during the time period of 1890 to 1935; a time when colonial sanitary government expanded with an extensive array of legislation, local ordinances, and measures to control epidemics. I used historical analytical methods based upon colonial records of law, reports from the Sanitary Commission, minutes from local government meetings, and gazetteers to trace how the colonial state used various legal tools including the Epidemic Diseases Act of 1897, local sanitation ordinances and vaccination requirements as ways to expand their administrative authority over the Indian body, dwelling place and urban space. The results show that both the law and its administration were dual-purpose: addressing real public health issues including plague, cholera, and malaria; and supporting the establishment of racial hierarchies, expanding the authority of the bureaucracy and exercising disciplinary power over Indian populations using the cover of modern hygiene. Additionally, this paper examined how Indian political actors, members of the municipal boards, and nationalist leaders in the United Provinces challenged, utilized, and reframed these sanitary laws to articulate demands for self-government and social reform. Ultimately, the research shows that the public health law in colonial UP was not simply a technical response to a disease issue but was a constitutive part of the state's power to define the limits of sovereignty, citizenship, and resistance in late colonial India.